Comparison of Slow and Forced Vital Capacity on Ability to Evaluate Respiratory Function in Bulbar-Involved Amyotrophic Lateral Sclerosis - Huang, Xin; Du, Chenfang; Yang, Qiong; Fan, Dongsheng (Frontiers in Neurology, 2022)
Background and Objective The percent-predicted forced vital capacity (FVC%) in the pulmonary function test (PFT) is generally used to evaluate the respiratory function in amyotrophic lateral sclerosis (ALS). The slow vital capacity (SVC) is another method to evaluate the respiratory function. Some neurologists found that the FVC% was not reflective of respiratory symptoms and the percent-predicted SVC (SVC%) was found to be higher in some patients with bulbar-onset ALS. We aimed to compare the percent predicted SVC (SVC%) with FVC% in evaluating the respiratory function and investigate the associations between the associations between clinical characteristics and the difference between the SVC% and the FVC% (SVC%-FVC%) in bulbar-involved ALS patients. Method This prospective study included patients with bulbar-involved ALS who visited the Peking University Third Hospital between October 2020 and November 2021. They underwent comprehensive clinical assessments, including bulbar symptom assessments, revised ALS functional rating scale (ALSFRS-R), Rasch-Built Overall Amyotrophic Lateral Sclerosis Disability Scale (Roads), and PFTs. The group differences were analyzed using parametric and non-parametric tests. Results A total of 59 participants were initially enrolled, and 51 of them were included in the final analysis. In patients with bulbar-involved ALS, the SVC% (73.82 ± 21.95%) was significantly higher (p = 0.013) than the FVC% (71.42 ± 23.15%). After controlling for other relevant variables, a partial correlation analysis showed a significant correlation (r = −0.352, p = 0.041) between ALSFRS-R1 score and SVC%-FVC%. Conclusion Our prospective study found that the SVC% was significantly higher and more reflective of actual respiratory function than the FVC% in patients with bulbar-involved ALS. Furthermore, the severity of dysarthria was found to be positively correlated with SVC%-FVC%, providing a clinical marker for predicting SVC%-FVC%.